Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: 2000 à aujourd'hui; amériques; discipline; droit; droits des femmes*; dénonciations en ligne; metoo; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques; violences; violences sexistes et sexuelles

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux